Sexually Dimorphic Profiling of Osteoarthritis: A Comprehensive Metabolomic Dataset - Yuhan Zhang; Yonghui Jiang; Qixian Jia; Gengchen Feng; Ziyi Yang; Wei Zhang (Scientific Data)
Abstract Osteoarthritis (OA) is a chronic disease characterized by high morbidity, affecting multiple body systems and associated with systemic metabolic disorders. The clinical features of OA exhibit significant sexual dimorphism. However, the specific metabolic characteristics underlying this difference remain incompletely understood, with a notable lack of molecular risk factors related to OA. In this study, we established a cohort of 60 OA cases comprising different genders. Employing liquid chromatography-tandem mass spectrometry (LC-MS/MS), we performed untargeted metabolomics analyses on synovial membrane, synovial fluid, urine, and serum samples, obtained simultaneously from each patient. Following rigorous quality control, we successfully constructed and annotated a metabolic profile of OA encompassing multiple sample types. This dataset provides a foundation for further investigation into the impact of sex on OA at metabolic level. Additionally, these findings are expected to enhance the study of potential sex-related biomarkers in OA and offer novel insights into clinical gender-specific management strategies.